International human resource management in multinational companies: Global norm making within strategic action fields. (12th December 2021) - Edwards, Tony; Almond, Phil; Murray, Gregor; Olga Tregaskis,
Abstract: The formation of global norms that affect work is a crucial element to how multinational companies (MNCs) achieve a degree of HR integration internationally. We establish a 'strategic action fields' framework to guide research into global norm‐making in MNCs in general and for analysing the work of those that we term 'globalising actors'—those who are active in globalising a firm's management of its human resources—in particular. We position our framework with relation to existing research in international human resource management, and show how the field can benefit from achieving an approach to global norm‐making that is contextualised, personalised and contested.